Taḥlīlu al Insāniyyati fī Riwāyati al Faḍīlati li Muṣṭafā Luṭfī al Manfaluṭī (Dirāsatun Taḥlīliyyatun fī ‘Ilmi al Ijtimā’i al Adabī) - Anggraini, Citra Dewi Nur; Nurlaily, Nurlaily (Al-Uslub: Journal of Arabic Linguistic and Literature, 2022)
Al-fadhilah novel is an adaptation of an original novel in French. The novel presents life on Mauritius island, Africa. The value of humanism presented in the novel is a criticism that alludes to colonial Europe at that time. This study aims to analyze the value of humanism in the novel. The research method used in descriptive qualitative with the type of library research. Data obtained through novel, internet and other sources. In this study, the researcher obtained some data from the novel. Among them a re two data in the literary aspect which is a picture of life at that time. The values of humanism in the novel are cooperation, mutual help, social solidarity, sympathy, kindness and mutual advice.